A Study to Show Correlation Between Blood Groups and Intelligence Level Among Medical Students - Noreen Farid, Faqir Ullah, Ghulam Muhayudin, Anwar Ali, Bilal Masood, Gul Maria, Ijaz Aziz, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: The connection between physiological characteristics, such as blood groups, and cognitive abilities has been the subject of scientific inquiry. Objectives: To investigate the possible relationship between blood groups and intelligence levels among medical students. Study Design: Cross-sectional analytical study Place and Duration: Conducted at HiTech University in Taxila, Punjab from January 2022 to January 2023. Methods: 240 medical students from HiTech University in Taxila, Punjab, participated in this cross-sectional, analytical study. Anti-A, anti-B, and anti-D antigens were used to determine blood classification. Stanford-Binet Intelligence Scale, Fifth Edition (SB5) was used to evaluate cognitive abilities in five domains: knowledge, quantitative reasoning, spatial processing, working memory, and fluid reasoning. Results: Demographic distributions exhibited significant variations in age, gender, year of study, location, and family background. Blood group distributions based on gender revealed the higher prevalence of B+ and O+ in females. SB5 domains exhibited nuanced differences in cognitive performance among participants of different blood groups. Blood group and cognitive domain correlation coefficients ranged from 0.08 to 0.12, with p-values indicating marginal significance. Conclusion: The research provided insight into the potential relationship between blood groups and cognitive abilities. It was found that blood groups are not reliable predictors of cognitive performance, highlighting the need for future research to evaluate the broader genetic and environmental context. Keywords: Blood groups; Cognitive abilities; Genetics Intelligence levels; Medical students; Stanford-Binet Intelligence Scale.